(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2020)
The article poses a thesis that the distinctive features of Polish philosophical and social thought are educational criticism, practicalism, activism, elitist egalitarianism, as well as religiousness. What is more, Polish philosophy focuses on man and his journey to perfection. The article stresses the importance, or even necessity, of developing Polish philosophy, which should be done in a European context. The author of the article believes that Polish philosophy may provide a humanistic basis for educating Poles. He supports his ideas with selected approaches to Polish philosophy from the early 20th century.